2019
DOI: 10.1515/forum-2018-0285
|View full text |Cite
|
Sign up to set email alerts
|

Abstract bivariant Cuntz semigroups II

Abstract: AbstractWe previously showed that abstract Cuntz semigroups form a closed symmetric monoidal category. This automatically provides additional structure in the category, such as a composition and an external tensor product, for which we give concrete constructions in order to be used in applications. We further analyze the structure of not necessarily commutative Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In particular, this product equips S, S with the structure of a (not necessarily commutative) Cu-semiring. These structures will be further analysed in a subsequent paper; see [APT18b].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this product equips S, S with the structure of a (not necessarily commutative) Cu-semiring. These structures will be further analysed in a subsequent paper; see [APT18b].…”
Section: Introductionmentioning
confidence: 99%
“…They defined the category normalCu of abstract Cuntz semigroups (also called normalCu‐semigroups) and showed that the process of assigning to each C‐algebra A the (concrete) Cuntz semigroup of its stabilization is a sequentially continuous functor. The properties of the category prefixCu and its relation with the category of C‐algebras was further developed in [3–5]. It is therefore interesting to seek efficient methods to compute the Cuntz semigroup of products and ultraproducts.…”
Section: Introductionmentioning
confidence: 99%
“…They defined the category Cu of abstract Cuntz semigroups (also called Cu-semigroups) and showed that the process of assigning to each C * -algebra A the (concrete) Cuntz semigroup of its stabilisation is a sequentially continuous functor. The properties of the category Cu and its relation with the category of C * -algebras was further developed in [APT18], [APT17], and [APT20]. It is therefore interesting to seek efficient methods to compute the Cuntz semigroup of products and ultraproducts.…”
Section: Introductionmentioning
confidence: 99%